Age at menopause and reproductive determinants in Polish women - Kaczmarek, Maria (Anthropological Review, 2001)
Selected reproductive determinants of age at menopause were analyzed using data from a representative sample of 4354 women aged 35-65 years. The data were collected in cross-sectional surveys carried out in Wielkopolska and Western part of Poland in the years 1998 to 2001. Menopausal status and median and mean ages at menopause were estimated with the use of retrospective and status-quo methods. It was found that the median age at natural menopause, estimated by probit analysis, was 50.1 years. Women, who had been treated with HRT (Hormonal Replacement Therapy) in the period of perimenopause, underwent menopause significantly later – their median age at menopause was 52.9 years. Results of ANOVA revealed that of all characteristics of female reproduction taken into consideration, age at menarche and length of menstruation cycle had significant influence on age at menopause. Menopause occurred markedly later in women who began to menstruate after 15 years of age and whose menstrual cycles lasted longer than 32 days. Reproductive determinants were considered as a complex factor. Stepwise multiple regression analysis with backward elimination revealed that the reproductive determinants including the length of menstruation cycle, age at menarche, age at first and last pregnancies and length of lactation in combination affected age at menopause.